Women's Barracks: The original 1950 tale of life and love in the free french army - Torres, Tereska; Mayne, Judith (The Feminist Press at CUNY, 2012)
This novel—based on the author's real-life experiences—is credited as the first candidly lesbian novel, originally published in 1950, that “scandalized mid-century America” (The New York Times).As the Blitz rains down over London, taboos are broken, affairs start and stop, and hearts are won and lost. This account of life among female Free French soldiers in a London barracks during World War II sold four million copies in the United States alone and many more worldwide. Women’s Barracks was banned for obscenity in several states and denounced by the House Select Committee on Current Pornographic Materials in 1952 as an example of how the paperback industry was “promoting moral degeneracy.” In spite of such efforts—or perhaps, in part, because of them—the novel became a record-breaking bestseller and inspired a whole new genre: lesbian pulp.Femmes Fatales restores to print the best of women’s writing in the classic pulp genres of the mid-20th century. From mystery to hard-boiled noir to taboo lesbian romance, these rediscovered queens of pulp offer subversive perspectives on a turbulent era.
Keywords: 1900-1999; 1940-1949; amour interdit; approches et analyses; europe; hétérosexisme; identités LGBTQIA2+; littérature; patriarcat; personnes lesbiennes; pulp lesbien; périodes historiques; royaume-uni; régions géographiques; sexualité; systèmes d'oppressions; thématiques

Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis